Semantic Ambiguity and Syntactic Bootstrapping: The Case of Conjoined-Subject Intransitive Sentences. Issue 1 (2nd January 2016) - Pozzan, Lucia; Gleitman, Lila R.; Trueswell, John C.
ABSTRACT: When learning verb meanings, learners capitalize on universal linguistic correspondences between syntactic and semantic structure. For instance, upon hearing the transitive sentence "the boy is glorping the girl, " 2-year-olds prefer a two-participant event (e.g., a boy making a girl spin) over two simultaneous one-participant events (a boy and a girl separately spinning). However, 2- and 3-year-olds do not consistently show the opposite preference when hearing conjoined-subject intransitive sentences ("the boy and the girl are glorping"). We hypothesized that such difficulties arise in part from the indeterminacy of the mapping between intransitive syntax and events in the world: a conjoined-subject intransitive sentence can be matched by the one-participant event (if "glorp" means "spin"), both events ("play"), or even the two-participant event ("fight"). A preferential looking study provided evidence for this hypothesis: sentences that plausibly block most non-target interpretations for novel verbs ("the boy and the umbrella are glorping") eliminated the asymmetric difficulty associated with conjoined-subject intransitives. Thus, while conjoined-subject intransitives clearly pose some special challenges for syntax-guided word learning ("syntactic bootstrapping") by novices (Gertner & Fisher, 2012), children's difficulties with this sentence type also reflect expected performance in situations of semantic ambiguity. In discussion, we consider the interacting effects of syntactic- and message-level indeterminacy.